Correlational Research on Mobile Phone Addiction and the Interpersonal Relationship Distress of Chinese College Students - He, Liming; Yang, Shaogang; Meng, Yangyang (ETHICS IN PROGRESS, 2023)
In this essay, we utilized the following scales: Mobile and Internet Addiction Test, Basic Psychological Needs Scale, Negative Coping Style Questionnaire, and Interpersonal Relationships Assessment Scale. With those, we surveyed 1,730 college students, investigating the influence of mobile phone addiction on their interpersonal relationship distress and the mediating chain effect of basic psychological needs and negative coping styles on mobile phone addiction and interpersonal relationship distress. The results indicate that: (1) Mobile phone addiction can predict interpersonal relationship distress in college students; (2) Basic psychological needs serve as the mediating variables between mobile phone addiction and interpersonal relationship distress; (3) Negative coping styles prove to be the mediator between mobile phone addiction and interpersonal relationship distress; and (4) Basic psychological needs and negative coping styles establish a mediating chain effect between mobile phone addiction and interpersonal relationship distress.